STRATEGIES OF PROMOTING WELL-BEING IN SCHOOL ACTIVITIES IN THE ROMANIAN EDUCATIONAL SYSTEM - Malureanu, Flavia; Enachi-Vasluianu, Luiza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The concept of well-being, although has been an issue of great relevance in the international literature and practice, is granted little time or attention in the Romanian educational system. As a matter of fact, teachers have to deal with overcrowded curriculum, not enough time to teach it, overcrowded classes with up to thirty or more students in the urban areas, especially. The only classes which lay little emphasis on well-being are those with disciplines which are not enlisted for the national exams, such as PE, Music, Arts.This paper aims to study a series of strategies meant to implement well-being in school activities. The selection of strategies was done according to specific literature, teachers’ systematic observations and experiences in the classrooms. The conclusions reached were that for students well-being is transposed into interactive fun activities with emphasis on discovery, experiment, role-playing, game, humour in all aspects of actions and communication, instructional activities out of the school area etc. Teachers’ discussions in focus-groups resulted into a questionnaire, used as an instrument to gather data.The research methods were the investigation based on questionnaire, the conversation and the systematic observation. The participants in the research were 100 teachers from two school levels: primary school (students 6-11 years old) and gymnasium (students 11-15 years old). Their experience in the didactic field varied from 2 to 15 years. The data collected were processed using the SPSS analysis. The results emphasized teachers’ awareness that the use of strategies of promoting well-being in school activities increase the efficiency of the educational activity.